(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents data on the state of collagen metabolism in terms of oxyproline in the blood, its clinical significance for assessing the severity and outcome of the disease, the criterion for the effectiveness of therapy in children of early age with acute obstructive bronchitis and bronchiolitis. The author recommends to determine the level of free and protein-bound oxyproline in blood plasma, an increase in which reflects the degree of destruction in the bronchopulmonary apparatus. The inclusion of immunomodulin into the basic treatment contributes to an increase in the effectiveness of therapy, a reduction of treatment duration.